1993
DOI: 10.1139/m93-124
|View full text |Cite
|
Sign up to set email alerts
|

Geosmin-producing species of Streptomyces and Lyngbya from aquaculture ponds

Abstract: 1993. Geosmin-producing species of Streptomyces and Lyngbya from aquaculture ponds. Can. J. Microbiol. 39: 834-840. Water and sediment samples collected monthly from six aquaculture ponds in east-central Alabama were analyzed for the presence of actinomycetes and cyanobacteria capable of producing geosmin and (or) 2-methylisoborneol, which cause earthy-musty off-flavors in fish. Six actinomycetous isolates were identified as geosmin producers, five of which were capable of producing 2-methylisoborneol. The one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Certain species of cyanobacteria are known to be responsible for the occurrence of off-flavor compounds (2-methylisoborneol (MIB), geosmin and b-cyclocitral) in water bodies, including species from the genera Oscillatoria (Matsumoto and Tsuchiya, 1988), Anabaena (Rosen et al, 1992), Microcystis (Jü ttner et al, 2010), Phormidium (Izaguirre, 1992), Lyngbya (Schrader and Blevins, 1993), and Pseudanabaena (Izaguirre and Taylor, 1998), imparting an undesirable earthy, musty, or muddy flavor to the fish.…”
mentioning
confidence: 99%
“…Certain species of cyanobacteria are known to be responsible for the occurrence of off-flavor compounds (2-methylisoborneol (MIB), geosmin and b-cyclocitral) in water bodies, including species from the genera Oscillatoria (Matsumoto and Tsuchiya, 1988), Anabaena (Rosen et al, 1992), Microcystis (Jü ttner et al, 2010), Phormidium (Izaguirre, 1992), Lyngbya (Schrader and Blevins, 1993), and Pseudanabaena (Izaguirre and Taylor, 1998), imparting an undesirable earthy, musty, or muddy flavor to the fish.…”
mentioning
confidence: 99%
“…The previous studies revealed that there was strain specificity in the ability of actinomycetes to produce odorous (Yagi et al 1987;Aoyama 1990;Schrader & Blevins 1993). In this study, Streptomyces, Micromonospora and Actinomadura, which are typical actinomycetes associated with odorous compounds, were all found in Tianjin fishponds (Gerber 1968(Gerber , 1969Wood et al 1983).…”
Section: Relationship Between Odorous Compounds and Species Of Actinomentioning
confidence: 63%
“…Morphological and phylogenetic analysis revealed that UIC 10445 was closely related to strains previously identified as Lyngbya wollei , a known producer of the neurotoxic saxitoxins, as well as the odor compounds geosmin and 2-methylisoborneol. (Carmichael et al, 1997; Foss et al, 2012; Schrader and Blevins, 1993; Watson et al, 2008) Recently, strains belong to the group of Lyngbya wollei were considered to form a separate genus described as Microseira . (McGregor and Sendall, 2015) Thus, UIC 10445 was identified as a Microseira sp.…”
Section: Introductionmentioning
confidence: 99%